(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article discusses the results of the degree of formation of social and psychological competencies, some formative factors of the empirical study of customs service employees. The article also reveals the model developed by the author, social and psychological competencies of customs service employees.